Experimental studies on the effect of neem seed powder (NSP) as a natural admixture in concrete. (2022) - Dharmaraj, R.; Anandaraj, S.; Sanjivnalan, N.; Sathish Kumar, S.; Shivash, N.; Srisharan, S.
Abstract: Many materials are utilised in building to partially substitute cement, such as fibre glass, ash, and so on. Concrete's consumption of cement might be reduced if NSP is utilised instead of Portland cement. Thus, CO2 emissions from cement manufacturing are kept to a minimum. The purpose of this research is to establish the suitability of NSP concrete M25 grade. The experimental research was divided into the following categories. The characteristics of the concrete components utilised in the mix design were determined through preliminary testing. The workability of NSP concrete, which was utilised in place of conventional concrete as a partial replacement, was tested using fresh concrete. Hardened concrete cubes, cylinders and prisms were used in experiments to assess the strength of the concrete when Neem seed powder was partially replaced, as required in IS 10262.The impact of varying proportioning's of NSP (0 %, 5 %, 10 %, 15 %, 20 %, and 25 %) on concrete performance has been investigated. Compressive strength properties of hardened concrete have been achieved after 3, 7, 14, 28, 56, and 90 days. The findings of 5% and 10% NSP were steadily increasing the strength at 28 days in this investigation.